DOZ047.01: Risk factors for anastomotic strictures in the first year after esophageal atresia repair: data from a prospective multicentric cohort. (24th June 2019) - Aumar, M; Rousseau, V; Bonnard, A; Sfeir, R; Gelas, T; Boubnova, J; Jacquier, C; Irtan, S; Breton, A; Guinot, A; Lamireau, T; Fouquet, V; et al.
Abstract: Objectives and study: Anastomotic stricture (AS) is a frequent complication of the surgery for œsophageal atresia (OA) during the first year of life. The primary objective of this study was to evaluate the prevalence of AS before 1 year old in infants with type A and C OA who were operated on. Secondary objectives were to determine risk factors for AS in OA, for recurrent and refractory AS, and to establish if AS is associated with antireflux surgery. Methods: A prospective national multicentric study was conducted including all infants born with OA between 2008 and 2015. Patients deceased before one year old, OA types B and E, and patients for whom data about AS were missing were excluded from the study. Data were collected at birth and at 12 months of age. Anastomosis under tension was defined by the surgeon and a delayed anastomosis was defined by an anastomosis after 15 days of life. Recurrent stricture was defined by the need of ≥3 dilations and refractory stricture was defined by the need of ≥5 dilations. Univariate and multivariate statistical analyses were conducted. Results: Of the 1258 eligible patients (84%), 1054 were included in the study from 38 centers. The prevalence of AS in the first year of life was 23.3% [20.7–28.9]. Anastomosis under tension (AUT) and delayed anastomosis (DA) were found to be independent risk factors for AS (respectively 2.5 [1.73–3.45] and 3.7 [1.95–7.2] (OR [CL 95%])) in the total population. Neither sex, birth weight, prematurity, intrauterine growth retardation, associated malformations, type A OA, nor the type of surgical approach was a risk factor for AS. In type C OA, DA was the only risk factor for AS (OR: 3.1 [1.65–5.86]). The group with AS had 2.5-fold more fundoplication compared to the patients without AS ( P  = 0.0005) in the total population and in type C OA. AUT and DA were found to be independent risk factors for recurrent stricture (OR: 2.4 [1.47–3.9] and 4.7 [2.2–10.4], respectively) and DA was the only risk factor for refractory stricture (OR: 6.23 [2.4–16.2]). Conclusion: Surgical factors at the time of first repair of OA are the only risk factors for AS.